2014
DOI: 10.1136/injuryprev-2014-041314
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gasoline price and patterns of motorcycle fatalities and injuries

Abstract: Our findings suggest that increasing gasoline prices led to more motorcycle riders on the roads and, consequently, more injuries. Aside from mandatory helmet laws and their enforcement, other strategies may include raising risk awareness of motorcyclists and investment in public transportation as an alternative transportation modality to motorcycling. In addition, universally mandated training courses and strict licensing tests of riding skills should be emphasised to help reduce the motorcycle fatal and non-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
(7 reference statements)
1
9
0
Order By: Relevance
“…ARIMA models have been widely developed to analyze time-series data in previous traffic safety studies (Friedman et al 2007; Martinez-Schnell and Zaidi 1989; Quddus 2008; Ramstedt 2008). Prior studies of gasoline prices and motorcycle safety have used ARIMA models to estimate the association of gasoline prices on motorcycle outcomes (Hyatt et al 2009; Wilson et al 2009; Zhu et al 2015). ARIMA models are also appropriate to address serial correlation in the data (Becketti 2013; Box et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARIMA models have been widely developed to analyze time-series data in previous traffic safety studies (Friedman et al 2007; Martinez-Schnell and Zaidi 1989; Quddus 2008; Ramstedt 2008). Prior studies of gasoline prices and motorcycle safety have used ARIMA models to estimate the association of gasoline prices on motorcycle outcomes (Hyatt et al 2009; Wilson et al 2009; Zhu et al 2015). ARIMA models are also appropriate to address serial correlation in the data (Becketti 2013; Box et al .…”
Section: Methodsmentioning
confidence: 99%
“…Hyatt et al (2009) suggested that gasoline prices were positively associated with population-adjusted rates of motorcycle injuries and fatalities, although there was no significant association after adjusting for the number of registered motorcycles on the road. Zhu et al (2015) found that motorcycle fatal and non-fatal injuries were highly correlated with increasing gasoline prices for the state of California.…”
Section: Introductionmentioning
confidence: 99%
“…[85][86][87][88][89][90][91]. On the other hand, the records were, also, not correlated, with basic information such as policies to ease purchase of vehicles, price of gas, motorcyclist's perceptions and preferences for using a type of vehicle, among others [92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that raising gasoline prices increased the number of motorcycle riders on the roads and, consequently, caused more motorcycle injuries. They indicated that besides the mandatory helmet use law, implementing ways to raise risk awareness of motorcyclists, investment in alternative transportation modes like public transportation and making strict licensing tests of riding skills would help to reduce the motorcycle fatal and non-fatal injuries (19). Hyatt et al, conducted a study to evaluate the association between increases in gasoline price for automobile occupants and motorcycle riders and motor vehicle collision-related injury and fatality rates; they reported that although the number of injuries and fatalities in motorcycle-related crashes increased with increasing gasoline price, rates of motorcycle-related injuries and fatalities per registered vehicles remained unchanged.…”
Section: Introductionmentioning
confidence: 99%